Vigabatrin-associated brain abnormalities on MRI in tuberous sclerosis complex patients with infantile spasms: are they preventable?. (December 2022) - Wan, Lin; He, Wen; Wang, Yang-Yang; Xu, Yong; Lu, Qian; Zhang, Meng-Na; Wang, Qiu-Hong; Dun, Shuo; Liu, Li-Ying; Shi, Xiu-Yu; Wang, Jing; Hu, Lin-Yan; et al.
Background: Vigabatrin (VGB) is currently the most widely prescribed first-line medication for individuals with infantile spasms (IS) and especially for those with tuberous sclerosis complex (TSC), with demonstrated efficacy. Meanwhile, its adverse events, such as vigabatrin-associated brain abnormalities on magnetic resonance imaging (MRI; VABAM), have also been widely reported. Objectives: The objectives of this study were to observe the occurrences of VABAM in patients with IS caused by TSC (IST) and further explore the associated risk factors. Methods: Children with IS receiving VGB were recruited from our institution; clinical, imaging, and medication data were collected. Cerebral MRI was reviewed to determine the occurrence of VABAM. Group comparisons (IS caused by TSC and other etiologies) were performed; subgroup analyses on IST were also performed. Next, a retrospective cohort study of children taking VGB was conducted to explore risk/protective factors associated with VABAM. Results: The study enrolled 172 children with IS who received VGB. VABAM was observed in 38 patients (22.1%) with a peak dosage of 103.5 ± 26.7 mg/kg/day. Subsequent analysis found the incidence of VABAM was significantly lower in the 80 patients with IST than in the 92 patients with IS caused by other etiologies (10% versus 32.6%, p -value < 0.001). In subgroup analyses within the IST cohort, VABAM was significantly lower in children who received concomitant rapamycin therapy. Univariate and multivariate logistic regression analysis of the 172 IS children showed that treatment with rapamycin was the independent factor associated with a lower risk of VABAM; similar results were observed in the survival analysis. Conclusion: The incidence of VABAM was significantly lower in IST patients. Further research is needed to examine the mechanisms that underlie this phenomenon and to determine if treatment with rapamycin may reduce the risk of VABAM.